Peran Personil Sekolah dalam Pelaksanaan Bimbingan dan Konseling - Salsabila Arsih; Firman Firman; Neviyarni Neviyarni; Muhammad Asyraf bin Che Amat (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This research aims to determine the urgency of collaboration between school personnel in implementing guidance and counseling services at schools. The successful implementation of guidance and counseling services in schools cannot be separated from the cooperation of all school personnel. The success of counseling can support the achievement of educational goals for students at school. This research method is a literature study. Data collection is carried out through a number of library data, recording and managing research materials. Based on the results of the research conducted, it shows that the collaboration carried out by the school principal, homeroom teacher and class teacher in implementing guidance and counseling services at school has not been optimal. One of them can be seen from the cooperation of school personnel in providing or receiving input and suggestions, openly exchanging ideas or discussing with each other.